Needs Analysis of the Use of Digital Supplementary Books on Social Character Material for Civic Education at the Junior High School - Anggraini, Nyimas Nuria Hasnah; Chotimah, Umi; Syarifuddin, Syarifuddin (Universitas Sebelas Maret, 2023)
This study aims to analyze the need for digital supplement books using the Flip Html5 application in civic education subjects in grade VII junior high school. Especially in Pancasila and civic education, learning activities that encourage the integration of character values can be implemented. Ideally, to achieve student self-development, the school can fulfill needs that will assist students in carrying out various educational activities, particularly learning activities, including teaching materials. At this stage, researchers made observations and collected data related to digital books. To collect data for this study, qualitative data types were used in the questionnaires. The data analysis technique employed was descriptive analysis with data reduction, data presentation, conclusion drawing, and verification. The data that researchers should analyze were the types of teaching materials used, the implementation of learning, evaluation systems, and the factors supporting them. Based on the needs analysis questionnaire, data were obtained that 90.1% of students stated they liked reading books containing writings and pictures, and 90.7% of students stated that they required additional knowledge besides package books. In addition, 59% of students preferred to find material through smartphones, and 82.7% answered that they were interested in reading digital books as additional material in the civic education learning process in grade VII SMPN 33 Palembang. Thus, to help the development of instructional resources that support enhancing the quality of learning, digital books can be an alternative.